2020
DOI: 10.1128/aac.00608-20
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of PIK-24 on Respiratory Syncytial Virus Entry by Blocking Phosphatidylinositol-3 Kinase Signaling

Abstract: Phosphoinositide-3 kinase signaling modulates many cellular processes including cell survival, proliferation, differentiation, and apoptosis. Currently, it is known that the establishment of respiratory syncytial virus infection requires phosphoinositide-3 kinase signaling. However, the regulatory pattern of phosphoinositide-3 kinase signaling or its corresponding molecular mechanism during respiratory syncytial virus entry remains unclear. Here, the involvement of phosphoinositide-3 kinase signaling in respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…We use the identification of 396 high confidence targets by CLEAR-CLIP combined with gene expression analysis of miR-27 modulated cells to systematically demonstrate the functionality of targets of miR-27 detected in our study in lung epithelial cells. We show that the inhibition of miR-27 activity by RSV is associated with upregulation of pathways important for RSV infection and replication including PI3K/Akt and MAPK signalling as well as control of cell cycle (67,(77)(78)(79)(80)(81)(82)(83). In addition, we identify as direct miR-27 targets the cytokine CSF1 as well as the chemokine CXCL2 which play important roles in intercellular communication (84).…”
Section: Discussionmentioning
confidence: 86%
“…We use the identification of 396 high confidence targets by CLEAR-CLIP combined with gene expression analysis of miR-27 modulated cells to systematically demonstrate the functionality of targets of miR-27 detected in our study in lung epithelial cells. We show that the inhibition of miR-27 activity by RSV is associated with upregulation of pathways important for RSV infection and replication including PI3K/Akt and MAPK signalling as well as control of cell cycle (67,(77)(78)(79)(80)(81)(82)(83). In addition, we identify as direct miR-27 targets the cytokine CSF1 as well as the chemokine CXCL2 which play important roles in intercellular communication (84).…”
Section: Discussionmentioning
confidence: 86%
“…Several studies reported that the viral penetration into host cells depends on PI3K signaling activation, and the PI3K activity requires, in turn, the activation of RhO-family GTPases and actin cytoskeleton reorganization. The role of the PI3K signaling results from the evidence that an impaired activity or inhibition of PI3K affects RSV replication ( 31 ).…”
Section: Rsv Structure and Host Cell Interactionmentioning
confidence: 99%
“…CC-BY-NC-ND 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted November 16, 2020. ; https://doi.org/10.1101/2020.11.14.382770 doi: bioRxiv preprint 4 series of compounds were found to exhibit potent antiviral activities [6][7][8][9][10] . In this paper, we report a plant-derived small molecule, 6,8-dihydroxy-9-isobutyl-2,2,4,4-tetramethyl-7-(3-methylbutanoyl)-4,9-dihydro-1H-…”
mentioning
confidence: 99%
“…As an ongoing research interest of our group in the past decades, we have constructed an in-house compound library composing of structural diversity natural products obtained from approximately 100 species of medicinal plants. After systematic bioassay screening, a series of compounds were found to exhibit potent antiviral activities 610 . In this paper, we report a plant-derived small molecule, 6,8-dihydroxy-9-isobutyl-2,2,4,4-tetramethyl-7-(3-methylbutanoyl)-4,9-dihydro-1 H -xanthene-1,3(2 H )-dione (rhodomyrtone, Fig.…”
mentioning
confidence: 99%